Masked vitamin B12 deficiency in pernicious anaemia: A diagnostic trap due to assay interference—Case report - Mohammed Abdulgayoom (14777791) (2025)
Megaloblastic anaemia is mainly caused by vitamin B12 or folate deficiency. However, rare cases present with discordant laboratory findings, particularly falsely elevated vitamin B12 levels due to assay interference from anti-intrinsic factor antibodies, complicating diagnosis and management. We describe a 64-year-old woman with macrocytic anaemia, pancytopaenia, and megaloblastic changes on the blood smear, yet with a markedly elevated serum B12 (>2000 pmol/L). A strongly positive anti-intrinsic factor antibody titre explained the paradoxical result. Empirical parenteral B12 therapy led to rapid haematological recovery, confirming masked B12 deficiency secondary to pernicious anaemia. This case highlights the critical pitfall of anti-intrinsic factor antibody-mediated assay interference in vitamin B12 testing, which can mask true deficiency. Clinicians must maintain a high index of suspicion for masked B12 deficiency in patients with megaloblastic anaemia and incongruent laboratory results, particularly in the presence of anti-intrinsic factor antibodies. Other Information Published in: SAGE Open Medical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/2050313x251377211